2018
DOI: 10.6118/jmm.2018.24.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Postmenopausal Women in Urban and Rural Communities

Abstract: ObjectivesMenopause is a transitional time in a woman's life leading to both physical and emotional challenges which affects the quality of life (QOL). Average age of menopause is around 48 years but it strikes Indian women at the age of 40 to 45 years. So, menopausal health demands higher priority in Indian as well as global scenario. The present study was conducted to compare the QOL of postmenopausal women residing in urban and rural communities.MethodsThe study adopted quantitative research approach with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This is in tandem with the study of African American white and Indian women in the late reproductive years (Menopause). The researchers found that the average age of menopause is 47 and 48 years respectively [9,14]. These findings are also similar to the study of Yisma, et al [15], where they found that globally the average age of menopause varies across geographic regions.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…This is in tandem with the study of African American white and Indian women in the late reproductive years (Menopause). The researchers found that the average age of menopause is 47 and 48 years respectively [9,14]. These findings are also similar to the study of Yisma, et al [15], where they found that globally the average age of menopause varies across geographic regions.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…Osteoporosis is one of major public health problem, responsible of low bone mass and bone fragility. This disease can induce pain and reduce physical activity leading to social isolation, depression and altered QoL [ 5 6 12 13 14 15 16 17 ]. Many studies are focused on assessing the QoL and depression in osteoporotic elderly women with fractures but few researches are published about physical and psychological status in PMW with osteoporosis in absence of fractures [ 8 17 18 19 20 21 22 23 24 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a systemic disease in which bone mineral density (BMD) is reduced with increased vulnerability to fractures. Social consequences, psychological difficulties and an impact on quality of life (QoL) with and without fractures can be observed [ 1 2 3 4 5 6 ]. Osteoporosis, as a vulnerable transition period, may induce pain, lead to mobility reduce and daily activities limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] These physiological, emotional, and psychological changes vandalize the health of these vulnerable females in total and reduce their quality of life (QoL). [ 3 ] Postmenopausal women are also at the highest risk of developing osteoporosis, since their bone mineral density is reduced as a result of a decrease in the estrogen level. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%